2003
DOI: 10.1292/jvms.65.1233
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Pathological Study on Canine Necrotizing Meningoencephalitis and Granulomatous Meningoencephalomyelitis

Abstract: ABSTRACT. Canine necrotizing meningoencephalitis (NME) and granulomatous meningoencephalomyelitis (GME) were compared pathologically. Gross observation exhibited lateral ventricular dilation and discoloration, malacia and/or cavitation of the cerebrum in NME. On the contrary, gross changes were milder in GME, except for occasional visible granulomatous mass formation. Histopathologically, the lesions of NME were distributed predominantly in the cerebral cortex and various degrees of inflammatory and necrotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
66
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 23 publications
8
66
0
4
Order By: Relevance
“…While the pathogenesis of NME is unclear, Uchida et al [22] and our previous report [12] demonstrated that dogs with NME possessed anti-astrocyte autoantibodies in their cerebrospinal fluids (CSFs), suggesting that NME is an autoimmune disease. In addition, Suzuki et al [20] reported the immunoglobulin and complement deposition on astrocytes in an NME case, supporting the pathological roles of anti-astrocyte autoantibodies. In the present study, we identified a common autoantigen for the anti-astrocyte autoantibodies in CSFs from Pug dogs with NME.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…While the pathogenesis of NME is unclear, Uchida et al [22] and our previous report [12] demonstrated that dogs with NME possessed anti-astrocyte autoantibodies in their cerebrospinal fluids (CSFs), suggesting that NME is an autoimmune disease. In addition, Suzuki et al [20] reported the immunoglobulin and complement deposition on astrocytes in an NME case, supporting the pathological roles of anti-astrocyte autoantibodies. In the present study, we identified a common autoantigen for the anti-astrocyte autoantibodies in CSFs from Pug dogs with NME.…”
mentioning
confidence: 78%
“…Histopathology of NME is characterized by lymphocytic inflammation and subsequent necrosis in the cerebral cortex [20]. While the pathogenesis of NME is unclear, Uchida et al [22] and our previous report [12] demonstrated that dogs with NME possessed anti-astrocyte autoantibodies in their cerebrospinal fluids (CSFs), suggesting that NME is an autoimmune disease.…”
mentioning
confidence: 96%
“…However, accurate diagnosis still requires histological analysis of brain tissue. Granulomatous meningoencephalitis (GME) is a delayed-type, T-cell dependent allergic response in the brain tissue [22]. Additionally, necrotizing meningoencephalitis (NME) is an autoimmune disease that affects brain tissue [13,25,27].…”
mentioning
confidence: 99%
“…Cães de outras raças pequenas também podem ser acometidos por encefalopatias necrotizantes, visto que a doença MEN já foi relatada em cães das raças Maltês (STALIS et al, 1995) e Papillon (SUZUKI et al, 2003), além da doença Leucoencefalite Necrotizante (LEN) que foi relatada em cães das raças Pequinês (CANTILE et al, 2001) e Yorkshire Terrier (TIPOLD et al, 1993). Na LEN, o tipo de lesão histológica se assemelha ao da ECP, diferenciando-se pela localização preferencial das lesões.…”
unclassified
“…Na LEN, o tipo de lesão histológica se assemelha ao da ECP, diferenciando-se pela localização preferencial das lesões. Estas não ocorrem na substância cinzenta do córtex cerebral, mas sim no tronco encefálico (SCHATZBERG et al, 2005 KUWABARA et al, 1998;STALIS et al, 1995;SUZUKI et al, 2003). Por meio do exame necroscópico, podem ser visualizadas áreas pseudocísticas no córtex cerebral.…”
unclassified